Visual Management Tools Sebagai Upaya Peningkatan Mutu Layanan bagi Manajer Pelayanan Rumah Sakit - Adila Kasni Astiena; Rika Ampuh Hadiguna; Acim Heri Iswanto; Hardisman Hardisman; Rima Semiarty; Fadilla Azmi (Warta Pengabdian Andalas, 2021)
The main issue of outpatient services at the Hospital in Padang-West Sumatra is the lack of use of Visual Management Tools (VMT). VMT is a tool to monitor service bottlenecks such as long waiting times. The devotee has designed an application-based VMT. This community service aims to assess the level of user satisfaction related to the application. Activities were carried out by socializing, designing, simulating and evaluating the application that can be downloaded on the Playstore. The target group was hospital officers and patients. They were trained to use the application and then evaluated. The sample consists of 80 people. The result of the community service was the training of officers related to several VMT tools in the form of Value Stream Map, Eight waste, Five why's, Failure Mode and Effect Analysis (FMEA) and Outpatient Service Applications. The variables were usability, ease of use, ease of learning, display quality, user-friendliness, completeness of information and flexibility. The level of satisfaction was in the category of satisfied and very satisfied. It was recommended to use modules to facilitate patient understanding using applications and services in hospitals.